Learning and Transferring Implicit Knowledge of Object Properties Across Robots via Interactive Perception - Tatiya, Gyan. (Tufts University. Tisch Library., 2024)
Thesis (Ph.D.)--Tufts University, 2023.; Submitted to the Dept. of Computer Science.; Advisor: Jivko Sinapov.; Committee: Elaine Short, Robert Jacob, Jason Rife, and Jonathan Francis.; Keywords: Computer science, Artificial intelligence, and Robotics.